2008
DOI: 10.1002/ange.200703753
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Tyrosyl Biradical in Mouse R2 Ribonucleotide Reductase from High‐Field PELDOR

Abstract: Paramagnetische Zentren in einer starren Proteinumgebung dienen als Sonden bei Strukturuntersuchungen von makromolekularen Komplexen. Durch Puls‐EPR‐Spektroskopie mit hohen Frequenzen erhält man nicht nur den Abstand, sondern auch Informationen über die relative Orientierung der Zentren (z. B. von Tyrosylradikalen; C grau, O rot, N blau). Die Methode ist aussichtsreich für Untersuchungen an Proteinkomplexen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…High field EPR has been driven by many motives, including interest in accessing faster time scales, increased spectral resolution and sensitivity, and the ability to study high-spin species with zero-field splittings too large to be observed at low fields [35]. Pulsed Dipolar Spectroscopy has been implemented at several fields above 0.35 T, which allowed demonstration of improvements in sensitivity [36,37], and offers the capability to perform orientation selective measurements [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…High field EPR has been driven by many motives, including interest in accessing faster time scales, increased spectral resolution and sensitivity, and the ability to study high-spin species with zero-field splittings too large to be observed at low fields [35]. Pulsed Dipolar Spectroscopy has been implemented at several fields above 0.35 T, which allowed demonstration of improvements in sensitivity [36,37], and offers the capability to perform orientation selective measurements [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…By this procedure in one case the unknown dimer structure was determined, because the location of the tyrosyl radical within the monomer unit was known from X-ray crystallography (Denysenkov et al, 2008). In another case, where the dimer structure was already known from X-ray crystallography, a fine-tuning of the tyrosyl molecule in its radical state in the protein environment was possible, and the results were in perfect agreement with ENDOR experiments performed on single crystals (Kolberg et al, 2005).…”
Section: G-band Peldor (High Magnetic Field)mentioning
confidence: 70%
“…PELDOR measurements at X-band frequencies allowed determination of the distance between the two tyrosyl radicals of the dimer (Bennati et al, 2005(Bennati et al, , 2003. At high magnetic fields (6.4 T), the anisotropy of the tyrosyl g-tensor is fully resolved, which allowed the measurement of the dipolar interaction for all different orientations of the tyrosyl radicals with respect to the external magnetic field (Denysenkov, Biglino, Lubitz, Prisner, & Bennati, 2008;Denysenkov et al, 2006). From this set of measurements, the orientation of the two tyrosyl radicals with respect to the interconnecting R vector could be extracted, enabling full determination of the dimer structure just from a single pair of tyrosyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Today it is a standard tool for distance determinations on the 1-10 nm length scale in many macromolecular systems, ranging from polymer and surface sciences to structural biology [17][18][19][20][21]. Nitroxide spin labels are most commonly used [22,23], but also natural occurring cofactors [24,25] amino acid radicals [26], [27] [28], metal centers [29,30], iron-sulfur clusters [31,32], or rare earth metal tags [33][34][35] have been used as paramagnetic centers.…”
Section: Introductionmentioning
confidence: 99%